Modeling Human Prostate Cancer Metastasis in Mice via Resection of Subcutaneous Allografts - Peiffer, Lauren B.; Hicks, Jessica; Sosa, Rebecca Y.; De Marzo, Angelo M.; Sfanos, Karen S.; Maynard, Janielle P. (Frontiers in Oncology, 2022)
The 5-year survival rate for patients diagnosed with distant metastatic prostate cancer in the United States is 30.6%. Therefore, there is a great need to develop in vivo model systems to study prostate cancer metastasis and to test potential therapeutics. Most murine prostate cancer metastatic models involve intracardiac or intraosseous implantation of cancer cells, which bypass early stages of tumor cell migration and invasion. Herein we provide a detailed protocol for a novel method of resecting subcutaneous prostate cancer allografts in immunocompetent mice to produce spontaneous metastases and describe a pilot study using this method of tumor resection. Intact male FVB/NCrl mice (n=9) were inoculated subcutaneously with Myc-CaP cells. Tumors were surgically resected, and mice were monitored for tumor recurrence. Animals were euthanized or died, and a full set of tissues were collected for histopathologic examination. Tumors took an average of 44 days (range 23-61) to reach 1.7 cm in any direction. All tumors were resectable, and resection of the tumors increased the study length by 70 days (range 30-121). One mouse was euthanized early of an unrelated cause, and of eight remaining mice, four developed tumor recurrence at the site of resection. One mouse developed bone metastases, one mouse developed metastases to the abdominal cavity, and two mice showed signs of local invasion. This study demonstrates that resection of subcutaneous Myc-CaP cell allografts in mice results in local tumor recurrence and the development of distant metastases, providing a new model system to study prostate cancer metastasis in vivo.